2007
DOI: 10.1007/s00239-007-9035-7
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Receptors for Growth Hormone and Somatolactin in Fish and Land Vertebrates: Lessons from the Lungfish and Sturgeon Orthologues

Abstract: Two cognate hormones, growth hormone (GH) and somatolactin (SL), control several important physiological processes in vertebrates. Knowledge about GH and its receptor (GHR) has accumulated over the last decades. However, much less is known about SL and its receptor (SLR). SL is found only in fish (including lungfish), suggesting that it was present in the common ancestor of vertebrates, but was lost secondarily in the lineage leading to land vertebrates after the lungfish branched off. SLR was suggested to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 50 publications
5
70
0
Order By: Relevance
“…Recent phylogentic and evolutionary analysis suggests that the SLR may in fact be a duplicated Ghr that occurred during the fish-specific genome duplication (Fukamachi & Meyer 2007). The striped bass ghr1 amplicon showed 70 and 72% nucleotide identity with medaka (Oryzias latipes; DQ002886; Fukamachi et al 2005), and masu salmon (Oncorhynchus masou; AB121047; Fukada et al 2005) slr respectively, while our striped bass ghr2 amplicon only showed 50 and 53% nucleotide identity to these same slr sequences.…”
Section: Jiaomentioning
confidence: 64%
“…Recent phylogentic and evolutionary analysis suggests that the SLR may in fact be a duplicated Ghr that occurred during the fish-specific genome duplication (Fukamachi & Meyer 2007). The striped bass ghr1 amplicon showed 70 and 72% nucleotide identity with medaka (Oryzias latipes; DQ002886; Fukamachi et al 2005), and masu salmon (Oncorhynchus masou; AB121047; Fukada et al 2005) slr respectively, while our striped bass ghr2 amplicon only showed 50 and 53% nucleotide identity to these same slr sequences.…”
Section: Jiaomentioning
confidence: 64%
“…Two transcripts (Genbank accessions: AF438177 and AY642116) were available in databases as GHR1 and GHR2, respectively. Fukamachi and Meyer (2007) demonstrated that sequences available in databases and reported as GHR (1 or 2) could be somatolactin receptors (SLR). We performed alignments of sequences, and unambiguously linked the sea bass GHR sequence to the transcript with accession AY642116 (GHR2, the alternate transcript being SLR; details not shown).…”
Section: Reverse Transcription and Quantitative Real-time Polymerase mentioning
confidence: 99%
“…According to sequence comparisons, it is generally believed that SL and PRL evolved from a common ancestral gene related to GH with two successive rounds of gene duplication before the divergence between vertebrates and invertebrates (Chen et al 1994, Fukamachi & Meyer 2007. However, the SL gene is not found in tetrapods and might have been lost during the evolution of early land vertebrates (Fukamachi & Meyer 2007).…”
Section: Introductionmentioning
confidence: 99%
“…According to sequence comparisons, it is generally believed that SL and PRL evolved from a common ancestral gene related to GH with two successive rounds of gene duplication before the divergence between vertebrates and invertebrates (Chen et al 1994, Fukamachi & Meyer 2007. However, the SL gene is not found in tetrapods and might have been lost during the evolution of early land vertebrates (Fukamachi & Meyer 2007). Fish SL is mainly expressed in the pars intermedia of the pituitary gland and distinct from proopiomelanocortin (POMC)-producing cells (Kaneko 1996); hence, it should have physiological actions different from those of GH and PRL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation